Distribution of macrozoobenthic taxa - potential indicators of vulnerable marine ecosystems in the western part of Bering Sea. 1. Anadyr Bay area - Victor A. Nadtochy; Nickolay V. Kolpakov; Ilya A. Korneichuk (Известия ТИНРО, 2017)
Following recent tendencies in fisheries policy to ensure both sustainability of ecosystems and conservation of economically sustainable fisheries, protection of vulnerable resources with low direct economic value comes to the focus of fisheries management on ecosystem principles. One of the problems of modern fishing is a negative impact of bottom trawling because of destruction of benthic organisms vulnerable to mechanical impacts. This by-effect of fishing could affect negatively on functioning of bottom biocenoses, reproduction of exploited species, and decrease generally productivity of vulnerable marine ecosystems (VME). Potential VME indicators are determined for the area of the Anadyr Bay in the Bering Sea on the base of results of 4 benthic surveys using bottom sampler (1985, 2005) and bottom trawl (2008, 2012), as the most common species in some macrozoobenthic groups of epifauna. They are Gersemia rubiformis for soft corals, Myxilla incrustans , Halichondria panicea , Semisuberites cribrosa for sponges, Halocynthia aurantium , Boltenia ovifera for sea squirts, Cystisella saccata , Flustra foliacea for bryozoans, Chirona evermanni for barnacles, and Gorgonocephalus eucnemis for brittle stars. Their distribution is mapped. According to their life history and feeding habits, these species-indicators are divided onto two groups: immobile sestonophages (alcyonarians, sponges, ascidians, bryozoans, cirripedians) and mobile filtrators (brittle stars). The first group prevails on hard and mixed grounds mainly along southwestern and northeastern coasts of the Anadyr Bay at the depths of 80-90 m (sponges and bryozoans - to 250 m in the Navarin Canyon) with relatively warm water, active hydrodynamics and high biological productivity. The second group represented by G. eucnemis dominates on soft sediments in the central part of the Anadyr Bay with the depths of 50-270 m occupied by the cold water pool. Quantitative distribution of brittle star, on the one hand, and barnacles with sea squirts, on the other hand, is alternative to each other. On the contrary, barnacles, sponges and sea squirts have similar distribution of the biomass, being complementary species. Distribution patterns of all species-indicators are stable for many decades. However, biomass of some these species has changed in the southern Anadyr Bay between the similar surveys conducted in the 2008 and 2012: the mean biomass of barnacle Ch. evermanni and sea squirt H. aurantium had decreased in 6.5 and 3.7 times, respectively, whereas the mean biomass of sponges, brittle star G. eucnemis and sea squirt B. ovifera did not change. Bottom trawl fishery is not active in the northwestern Bering Sea, moreover, the habitats of immobile sestonophages with hard grounds are avoided by bottom trawlers being dangerous for fishing gears, so the observed decreasing of two species abundance is presumably caused by natural reasons or is a random error of the mosaic-distributed stocks assessment with insufficiently dense sampling grid.